Recent Developments in Mechatronics and Intelligent Robotics Proceedings of International Conference on Mechatronics and Intelligent Robotics (ICMIR2018) - Deng, Kevin; Yu, Zhengtao; Patnaik, Srikanta; Wang, John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book is a collection of proceedings of the International Conference on Mechatronics and Intelligent Robotics (ICMIR2018), held in Kunming, China during May 19-20, 2018. It consists of 155 papers, which have been categorized into 6 different sections: Intelligent Systems, Robotics, Intelligent Sensors & Actuators, Mechatronics, Computational Vision and Machine Learning, and Soft Computing. The volume covers the latest ideas and innovations both from the industrial and academic worlds, as well as shares the best practices in the fields of mechanical engineering, mechatronics, automatic control, IOT and its applications in industry, electrical engineering, finite element analysis and computational engineering. The volume covers key research outputs, which delivers a wealth of new ideas and food for thought to the readers. .
Keywords: Mechatronics; Control engineering; Robotics; Automation; Computational intelligence; Artificial intelligence; Mechatronics; Control, Robotics, Automation; Computational Intelligence; Artificial Intelligence